AI-Driven Thermal Image Analysis in Thermoplasmonics for Diagnosing Tissue Anomalies: Bridging Clinical Pharmacy and Nursing Care - Ravula, Sahithya Ravali; Mavaluru, Dinesh; Auguskani, Jerlin Priya Lovelin; Chellathurai, Amutha (Journal of Neonatal Surgery, 2025)
Artificial Intelligence and machine learning algorithms, paired with thermoplasmonics and thermal feedback, have newly transformed the detection and apply milt therapy when cells are territorial for human tissue abnormalities. AI-assisted thermal image analysis mechanism in clinical pharmacy and nursing care: A novel study that takes advantage of advanced algorithms, thermoplasmonics, can analyses tissue errors such as tumours, contagions, and irritation reactions with unmatched accuracy. The research also emphasizes the role of AI-generated insights in effective drug dosing tailored to individual patients and empowers nursing professionals with real-time information to streamline patient care processes, thereby helping clinical pharmacies. It also discusses ethical issues, implementation challenges, and possibilities for advancing the evolution of AI-enhanced thermoplasmonics in clinical care and nursing practice.